Monitoring the Muara Laboh Geothermal Field in Indonesia using the ISBAS Method with Sentinel-1 SAR Images - Mokhamad Yusup Nur Khakim; Takeshi Tsuji; Erni; Akhmad Aminudin Bama; Frinsyah Virgo; Muhammad Irfan; Azhar Kholiq Affandi; Toshifumi Matsuoka (Science and Technology Indonesia, 2023)
The Muara Laboh geothermal field lies in a South Solok basin zone, West Sumatra, Indonesia. Production and reinjection of geothermal fluids into the underground reservoir commonly induce crustal deformation. The study area is covered by 63.8% plantation, primary, and secondary forests, which limit the ability of conventional InSAR techniques. Therefore, an Intermittent Small BASeline Subset (ISBAS) analysis has been performed to estimate line-of sight (LOS) displacement time series due to geothermal production using the Sentinel-1 dataset between 8 March 2021 and 15 March 2022. The localized subsidence with âˆ¼30 mm/yr rate over this tropical geothermal field has been revealed by using the ISBAS. The subsidence coincides with an area of the Muara Laboh geothermal reservoir. We suggest that geothermal production induced subsidence. In addition, the deformation in this geothermal field was controlled by faults and seasonally influenced by rainfall. Therefore, deformation variation was correlated with fluctuations in rainfall patterns. The geothermal reservoir system exhibited elastic expansion in response to seasonal recharge events during the rainy season.